Implementasi Desain Interior Terhadap Kenyamanan Pemustaka Di Perpustakaan Pusat Universitas Negeri Padang (SENIMAN: Jurnal Publikasi Desain Komunikasi Visual, 2023)
The purpose of this research is to (1) Analyze the interior design factors that affect the comfort of library users in the layout on the second and third floors of the Padang State University Central Library. (2) Analyze the application of interior design layout to the comfort of library users on the second and third floors of the Padang State University Central Library. (3) Analyzing the obstacles in the application of interior design to the comfort of visitors on the second and third floors of the Central Library of Padang State University.This research uses descriptive research with a quantitative approach. The sample in this study were visitors to the Central Library of Padang State University using purposive sampling technique, the number of samples taken by researchers amounted to 20 samples. The types of data used are primary data and secondary data, techniques and data collection tools used questionnaires using a Liker scale to score each question item. The questionnaire was distributed directly to respondents who were met at the Padang State University Central Library.The results of this study are analyzing interior design factors that affect the comfort of the library users have an average score of more than 3.40 which means that the library users already feel comfortable in the Central library of Padang State University. Analyzing the application of interior design layout to the comfort of the library users has an average score of more than 3.50 which means that the library users already feel comfortable in the Central library of Padang State University. While analyzing the obstacles in the application of interior design to the comfort of the visitors with the results of an average score of more than 2.60 which means that they quite agree with the statement that there is still a lack in the application of walls, ceilings, and furnishings (furntutre). So additions and improvements are needed such as walls, ceilings and furniture in the Padang State University Central Library.